2022
DOI: 10.1002/cmdc.202100784
|View full text |Cite
|
Sign up to set email alerts
|

Antiparasitic Derivatives of the Furoquinoline Alkaloids Kokusaginine And Flindersiamine

Abstract: We report the synthesis of 16 new compounds obtained from kokusaginine and flindersiamine, the main alkaloids isolated from the bark of Balfourodendron riedelianum. The activity of the compounds against axenic cultures of Trypanosoma cruzi epimastigtotes and trypomastigotes, as well as intracellular amastigotes, is described, together with their cytotoxic activity against three different human cell lines. The synthetic strategy for the preparation of the new compounds was based on the reactivity at the C4 posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…The mechanism of their action might be related to epinephrine α receptors, the M-receptor, and the calcium channel receptor [ 61 ]. Derivatives of cocusaginine and flindersiamine, the primary alkaloids isolated from the bark of Balfourodendron riedelianum , have shown superior in vitro activity against Trypanosoma cruzi compared with positive controls [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of their action might be related to epinephrine α receptors, the M-receptor, and the calcium channel receptor [ 61 ]. Derivatives of cocusaginine and flindersiamine, the primary alkaloids isolated from the bark of Balfourodendron riedelianum , have shown superior in vitro activity against Trypanosoma cruzi compared with positive controls [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kokusaginine also displays modest cholinesterase inhibitory activities (IC 50 = 41.46 and 70.24 µg/mL against butyrylcholinesterase and acetylcholinesterase, respectively) [ 38 , 39 ]. The compound has been used as a starting point to the design of antiparasitic molecules active against Trypanosoma cruzi responsible for the Chagas disease [ 40 ]. Kokusaginine is an isomer of skimmianine and a close analogue of dictamnine, both furoquinolines commonly found in Ruta species and endowed with anticancer properties [ 41 , 42 , 43 ].…”
Section: Bioactive Phytochemicals From R Angustifolia ...mentioning
confidence: 99%
“…Indeed, more active and safer pesticides might be chemically derived from the compounds described here. For example, Valdez et al found that certain derivatives of kokusagenine (7) and flindersiamine (3) were more active against the human parasite Trypanosoma cruzi than the natural compounds without any cytotoxicity to three human cell types [41].…”
Section: Compounds Rankingmentioning
confidence: 99%